2016
DOI: 10.1111/imb.12247
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis provides insight into venom evolution in a seed‐parasitic wasp, Megastigmus spermotrophus

Abstract: One of the most striking host range transitions is the evolution of plant parasitism from animal parasitism. Parasitoid wasps that have secondarily evolved to attack plants (ie gall wasps and seed-feeders) demonstrate intimate associations with their hosts, yet the mechanism of plant-host manipulation is currently not known. There is, however, emerging evidence suggesting that ovipositional secretions play a role in plant manipulation. To investigate whether parasites have modified pre-existing adaptations to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…Furthermore, a morphological comparison of the venom apparatus in 25 species of Cynipoidea revealed that most gall inducing wasps have better-developed and more prominent structures than closely related parasitoid (i.e., non gall-inducing) wasps (Vårdal, 2006). This is compatible with the hypothesis that the venom of gall wasps could indeed be of functional importance in the interaction with the host plant, an issue recently addressed for other hymenopteran species interacting with plants such as fig wasps (Martinson et al, 2015; Elias et al, 2018) and a seed-parasitic wasp (Paulson et al, 2016).…”
Section: Introductionsupporting
confidence: 86%
“…Furthermore, a morphological comparison of the venom apparatus in 25 species of Cynipoidea revealed that most gall inducing wasps have better-developed and more prominent structures than closely related parasitoid (i.e., non gall-inducing) wasps (Vårdal, 2006). This is compatible with the hypothesis that the venom of gall wasps could indeed be of functional importance in the interaction with the host plant, an issue recently addressed for other hymenopteran species interacting with plants such as fig wasps (Martinson et al, 2015; Elias et al, 2018) and a seed-parasitic wasp (Paulson et al, 2016).…”
Section: Introductionsupporting
confidence: 86%
“…In a study to determine the bacterial symbionts associated with the seed-parasitic insect Megastigmus (Hymenoptera: Torymidae) Paulson, Von Aderkas & Perlman (2014) also found Ralstonia as the dominant bacteria genus. In a subsequent study of Megastigmus with transcriptome analysis, many mobile genetic elements transcripts from Ralstonia were discovered (Paulson et al, 2016), corroborating the association of this bacterial genus with Megastigmus. In spite of these results, no function of Ralstonia was determined in these insects and a gap still remains in the seed feeding insect microbiome which requires further study.…”
Section: Introductionmentioning
confidence: 68%
“…This genus has also been documented as an important and abundant member in the wasp microbiome (Paulson, Von Aderkas & Perlman, 2014) and also in the gut of Illeis koebelei ladybird beetles (Yun et al, 2014). Paulson, Von Aderkas & Perlman (2014) speculated that this bacterial genus could play an important role in nutrient recycling in Megastigmus wasps -which infest seeds to undergo their development -and latter documented that in the Megastigmus transcriptome the majority of bacterial annotation was represented by sequences from Ralstonia with highly expressed mobile elements (Paulson et al, 2016). It is interesting that Pheidole ants, the Megastigmus wasp and Harpalus pensylvanicus carabids, all with seed related lifestyles, harbor high abundance of Ralstonia and future studies focusing on the function or even location within the host are necessary to better understand these results.…”
Section: Main Bacteria Associated With Pheidolementioning
confidence: 99%
“…Parasitoid wasps often use venom to modify the metabolism of their hosts; toxins and their known or presumed biological functions are described in various species [43]. We investigated the presence of homologs of N. vitripennis toxin constituents in M. amalphitanum and other parasitoid wasps (Megastigmus spermotrophus, N. vitripennis, C. solmsi, T. pretiosum), using previously published venom data [44,45] and the transcriptomes of chalcid wasps (Table S6). We identified 28 transcripts encoding putative venom proteins (Figure 2; Table S9); homologs of these are found in all investigated Chalcidoidea species ( Table 2)…”
Section: Venom Components In the M Amalphitanum Transcriptomic Datamentioning
confidence: 99%